Efeitos distributivos do salário mínimo no Brasil recente: recortes segundo a posição na ocupação - Dias, Júnior César (2008)
The aim of this study is to estimate the impact of the changes in the minimum wage on the distribution of individual income from work, by position in the occupation registered workers (CC) unregistered workers (SC), self-employed (CP) and the set of all the occupied (CC + SC + CP) in the period 1995-2007. In order to do that we have used three complementary methodologies and the results confirm the positive distributional effects of the minimum wage especially among registered workers and workers who are not registered and it is more effective among the latter. In a visual and quantitative presentation, through the densities of kernel, the visible peaks in estimated densities illustrate the value of income equal to the minimum wage in almost all positions in the occupation, confirming, in a way, the evidence found in the literature. Furthermore, we note that the largest proportion of minimum wage receivers is among black women who are at home on the condition of wives or daughters and have a low educational level, besides working in the service sector as unregistered employees. Most of them live in the North and Northeast regions of the country. These results suggest that a large proportion of the income of individuals devoid of bargain wage maintains its purchasing power through the existence of the minimum wage. Accordingly, the minimum wage is proving an effective tool to protect workers who need protection in the labor market. Through the second and third methodological approaches, entitled differences in time differences by hundredth and regressions by hundredth, we try to quantify the impact of minimum wage on the income of each hundredth of the distribution. In the second approach, we try to capture changes in hundredth income which are derived from changes in the minimum wage. The results show that for some clippings and some groups of income, the calculation of the flexibility of the income when it comes to the minimum wage also coincides with the average recorded in the literature. For the third approach, regression by hundredth, we noticed that changes in minimum wage exert significant impacts on the occupied inserted into ranges of low incomes particularly among registered and unregistered workers. However, these changes have proved very important for freelance workers. These exercises strengthen the studies that argue that the minimum wage has an important lighthouse-like effect for a large contingent of unregistered employees, but we do not see this effect in the case of self-employed workers. However, it is important to emphasize that, despite the obstacles in the extrapolation of these results for the economy as a whole and for other periods, this seems to be a non-negligible evidence to indicate that the policy of minimum wage can be used as an instrument of economical policy. Indeed, given its importance as an instrument of distributional policy, we believe that increases in the value of the minimum wage can significantly modify the distribution of income of a country.